Synthesis and characterization of some novel 1,2,4-triazoles, 1,3,4-thiadiazoles and Schiff bases incorporating imidazole moiety as potential antimicrobial agents - Aouad Mohamed Reda; Messali Mouslim; Rezki Nadjet; Ali Adeeb Al-Sheikh; Lesimple Alain (Acta Pharmaceutica)
(1,4,5-Triphenylimidazol-2-yl-thio)butyric acid hydrazide (3) was obtained via alkylation of 1,4,5-triphenylimidazol-2- thiol (1) with ethylbromobutyrate, followed by addition of hydrazine hydrate. Treatment of acid hydrazide 3 with carbon disulfide in an ethanolic potassium hydroxide solution gave the intermediate potassium dithiocarbazinate salt, which was cyclized to 4-amino-5-[(1,4,5-triphenylimidazol- -2-yl)thiopropyl]-2H-1,2,4-triazole-3-thione (4) in the presence of hydrazine hydrate. Condensation of compound 3 with alkyl/arylisothiocyanate afforded the corresponding 1-[4-(1,4,5-triphenylimidazol-2-ylthio)butanoyl]-4-alkyl/arylthiosemicarbazides (5-7), which upon refluxing with sodium hydroxide, yielded the corresponding 1,2,4-triazole - -3-thiols 8-10. Under acidic conditions, compounds 4-6 were converted to aminothiadiazoles 11-13. Moreover, the series of Schiff bases 14-18 were synthesized from the condensation of compound 3 with different aromatic aldehydes. The newly synthesized compounds were characterized by IR, 1H NMR, 13C NMR and mass spectral analyses. They were also preliminarily screened for their antimicrobial activity.